Recoverable Concealed Data Aggregation with Multiple Applications in WSN (International Journal of Engineering and Computer Science, 2014)
Recently several data aggregation techniques based on symmetric key encryption mechanism have been proposed on wireless sensor networks (WSNs). These types of data aggregation methods result better security compared with the traditional aggregation mechanisms. In this proposed Recoverable Concealed Data Aggregation approach, Cluster Head (CH) can directly aggregate the cipher texts of an individual nodes present on that particular cluster. Based on symmetric schemes, the provider can conduct aggregation queries without decryption.  Here, a Concealed Data Aggregation (CDA) technique is extended with the symmetric key encryption. Also, the clustering strategy is presented to divide the sensor nodes into multiple clusters. Cipher Block Chaining (CBC) algorithm is used to encrypt the sequence of bits into a single block or unit. The proposed scheme has three contributions. First, it is designed for a multiple application environment. The base station retrieves the application-specific data from the aggregated cipher texts. Next, it mitigates the impact of compromising attacks in single application environments. Finally, it degrades the attacks from unauthorized aggregations. The result shows that the proposed Recoverable Concealed Data Aggregation with Multiple Applications (RCDA-MA) performs better than the existing CDAMA system.